2020
DOI: 10.1038/s41598-020-60825-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of methicillin-resistant Staphylococcus aureus: a multicentre study in China

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has become a serious threat to global health.In China, the proportion of S. aureus isolates that were MRSA was 44.6% in 2014. The clinical and economic impact of MRSA in China remains largely uninvestigated. This study aims to compare the differences in hospital costs, length of hospital stay, and hospital mortality rate between MRSA and methicillin-susceptible S. aureus (MSSA) colonization or infection and between MRSA cases and those without an S. aureus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 37 publications
(32 reference statements)
2
49
0
2
Order By: Relevance
“…In this study, the main indicators included economic costs, LOS, and in-hospital mortality. We performed 1000 iterations of Monte Carlo simulations to calculate the 95% uncertainty interval for each indicator with normal distribution using SAS [ 35 ]. We compared the main indicators between CRKP and CSKP group, between CRPA and CSPA group, between CRAB and CSAB group using t test and χ 2 test for quantitative and qualitative variables, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the main indicators included economic costs, LOS, and in-hospital mortality. We performed 1000 iterations of Monte Carlo simulations to calculate the 95% uncertainty interval for each indicator with normal distribution using SAS [ 35 ]. We compared the main indicators between CRKP and CSKP group, between CRPA and CSPA group, between CRAB and CSAB group using t test and χ 2 test for quantitative and qualitative variables, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The emergence and continuing spread of multi-resistant S. aureus strains, such as methicillin-resistant S. aureus (MRSA) and vancomycin-resistant S. aureus (VRSA), complicate the treatment of staphylococcal infections and cause a significant economic burden. For example, a multicenter study in China showed an average increase in hospital costs of 3182 USD to 6533 USD for MRSA patients as compared to methicillin-sensitive S. aureus (MSSA) patients [ 9 ]. Coupled to the fact that even reserve antibiotics fail to successfully treat severe S. aureus infections, it is not surprising that the WHO lists S. aureus as one of the major health threats in a so-called “post-antibiotic era” [ 10 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…Staphylococcus aureus ( S. aureus ) is considered one of the most common commensal bacteria that is usually found in the anterior nares of healthy individuals, but it is also a major pathogen that has been associated with serious community and nosocomial acquired infections, such as skin and soft tissue infections, pneumonia and bloodstream infections, which are associated with increased hospital mortality and morbidity [ 1 , 2 ]. The ability to develop resistance to various classes of antibiotics has brought more clinical attention to S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Soon after the introduction of methicillin, resistance emerged in certain strains of S. aureus, and these strains became famously described as methicillin resistant Staphylococcus aureus (MRSA), which was first isolated in the UK in the early 1960s [ 3 ]. Since then, the prevalence of MRSA has increased and it has been found that MRSA proportion constituted between 20% and 80% of all S. aureus isolates in different countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation